Grammar exercises in Dutch, Finnish and global textbooks for teaching German as a foreign language. Issue 5 (20th October 2019) - Maijala, Minna; Tammenga-Helmantel, Marjon
ABSTRACT: In foreign language (FL) teaching and learning, a substantial amount of content is provided in grammar exercises supplied by textbooks. The main focus of this study concerns the selection of grammar exercise types in FL textbook series. In our analysis, we focus on Dutch, Finnish and global textbooks for beginners aged approximately 13–15 years who are learning German (A0–A2 on the CEFR scale). Furthermore, an insight into the pedagogical approaches to grammar learning favoured in these textbooks is provided. The findings show that blank-filling exercises are the most frequently used exercise type in all the textbooks, with the amount ranging from 30.8% to 59.0%. The results of the analysis also indicate that the approach to learning grammar is a mixture of the Presentation-Practice-Production approach and strongly controlled learner-centeredness. Finally, based on the results of our study, we suggest that more variation within grammar exercises is required to meet the needs of different learners and their learning styles. Above all, we conclude that there is still a gap to be bridged between the reality in FL textbooks and the ideal presented in the research literature.